The Relationship Level of Self-Medication Knowledge with Rationality of Drug Use in Adolescents - Kusuma, Muhammad Cariefzi Zahdffa; Meiyanti, Meiyanti (Universitas Islam Bandung, 2024)
Currently, self-medication in Indonesian adolescents has a high prevalence. The problem with self-medication is the accuracy of drug use in adolescents, resulting in irrational treatment. The purpose of this study was to analyze the relationship between the level of knowledge of self-medication and the rational use of gastritis drugs in adolescents. This observational study has a cross-sectional design and a sample size of 91 students. The research was conducted from April to June 2021 in Jakarta. The nonrandom sampling method was used for the selection of research samples. Research data were obtained through interviews and questionnaires. Calculate the sample size using the infinite and finite population formula with a prevalence of 23.8. Inclusion criteria subjects aged 15–19 years who had complaints in the upper gastrointestinal tract and signed informed consent. Exclusion criteria are students taking gastritis treatment based on prescriptions from doctors or according to doctor's recommendations. Data analysis using SPSS 23.0 and correlation test using the chi-square test with a significance value of p<0.05. The results showed that 33% of respondents had good self-medication knowledge, and as many as 60% had irrational gastritis treatment behavior. The results of bivariate analysis obtained there is a significant relationship between the level of knowledge of self-medication and the rational treatment of gastritis with a value of p=0.000 (p<0.05). This study concludes that there is a relationship between knowledge of self-medication and the rational use of drugs.